Memperkenalkan Kembali Metode Eksperimen dalam Kajian Komunikasi - Setyanto, A. Eko (FISIP Universitas Atma Jaya Yogyakarta, 2006)
Abstract: This article remind us to use experiment method in communication reserach. Experimental method has some characteristic especially that researcher can control reserach variables. Author explain design types in experimentasl methods and how to do experiemental method. There are classical and factorial types in experimental methods.